Guidelines for Enhancing the Potential of Young Smart Farmers in Lamphun Province through BCG Economic Development Approach - Jarernpanit, Thannapat; Sunanta, Piyachat; Inprasertkul, Thanapol; It-ngam, Tosaporn; Jaitiang, Tassawan; Jaksu, Kanokthip (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
This article aimed to study the needs and potential of young smart farmers through the Lamnamrak Community Enterprise in Lamphun Province and to propose guideline for enhancing the potential of these farmers in the region following the BCG economic development approach. The study employed a qualitative participatory research method, targeting eight members of the new generation farmers’ group within the Lamnamrak Community Enterprise in Lamphun Province. The sample was selected using a purposive sampling method. The research tools included a needs assessment survey and focus group interviews to extract lessons learned regarding the group’s resources and potential. A participatory research process was also used to plan and design strategies for capacity development. The findings in relation to the first objective provided an assessment of the potential of the new generation farmers within the Lamnamrak Community Enterprise. For the second objective, the study presented guidelines for enhancing the capacity of young farmers in Lamphun Province based on the BCG economic model development. These guidelines included a capacity development curriculum for young farmers and entrepreneurs, along with recommendations for future research projects to further develop the group’s potential.